Analisis Beberapa Sifat Fisik Tanah Pada Tanaman Kelapa Sawit Di Desa Kuala Behe Kecamatan Kuala Behe Kabupaten Landak - Leony Agustine; Rini Hazriani; Ya' Muhamad Iqbal (Universitas Pekalongan, 2023)
This land suitability evaluation is basically used to determine the level of suitability of a plot of land for a particular use. Kuala Behe Village currently has quite good potential in developing large areas of community oil palm plantations. The aim of this research is to analyze several soil physical properties of oil palm plants in Kuala Behe Village, Kuala Behe District, Landak Regency and provide management recommendations. The method used in this research is land surveying and mapping. The research begins with a preliminary survey of the research location, then continues with making a map of observation points determined based on the distribution of land unit maps obtained from the overlay or overlap of administrative maps, slope class maps and soil type maps with reference to the physiographic survey method. The research location has an area of 120 ha consisting of 6 land units, then continued with carrying out activities in the field (observing the physical properties of the soil and taking soil samples according to the coordinate points that have been obtained). The analysis results showed that the dominant texture was clay with a medium texture class, the effective depth of the soil was included in the deep criteria, had good drainage, very deep sulfidic hazards, light erosion and no threat of flooding. The research location has 2 types of soil, namely Typic Dystrudepts and Fluventic Dystrudepts which are classified into 6 land units, namely land units with a total area of approximately 120 ha. Improvement efforts can be made by constructing drainage channels, constructing contour terraces and planting ground cover plants.